AN OVERVIEW ON ULTRA DEFORMABLE VESICULAR DRUG DELIVERY SYSTEMS IN TRANSDERMAL DRUG DELIVERY - POLA, KRANTHI KUMAR; KUMAR RADA, SANTOSH (International Journal of Applied Pharmaceutics, 2023)
Transfersomes are emerging carriersin transdermal applications owing to numerous benefits like ease of application, reduction in dose frequency, In this review, we will describe about the penetration mechanism of transfersomes, method to prepare the formulation and characterization of transferosomal formulation, like thin film hydration, vortexing sonication, modified handshaking, suspension homogenization, centrifugation, and ethanol injection apart from these characterizations include, vesicle size, shape zeta potential, in vitro, and in vivo to find out the optimized formulation charactering the transferosomal preparations chemical, physical and miscellaneous properties to meet the ideal requirements of formulation and achieve the grater bioavailability and to attain good stability. These formulations are gaining good importance as Novel Drug Delivery Systems because of their patient compliance, ultra deformable and flexible nature due to the presence of surfactants and other pharmaceutical excipients like cholesterol, phospholipids in the formulation; hence these are known as first-generation liposomes.